Pengaruh Employee Engagement dan Kepatuhan Kerja terhadap Komitmen Organisasi melalui Effort Reward Imbalance pada Tenaga Kesehatan RS. Harapan Sehat Slawi - Ica Ulfa Sausan; Erliany Syaodih; Budi Santoso (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of employee engagement and work compliance on organizational commitment through effort reward imbalance as a mediating variable in healthcare workers at Harapan Sehat Hospital, Slawi. The research method used is a quantitative approach with an explanatory research design. The research sample consisted of 92 respondents taken using proportional sampling technique with the Slovin formula from a total population of 120 healthcare workers. Data were collected through a Likert scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the help of SmartPLS to test the relationship between variables and the mediating effect. The results showed that employee engagement and work compliance have a positive and significant effect on effort reward imbalance, and each of these variables also has a direct effect on organizational commitment. In addition, effort reward imbalance was proven to be able to significantly mediate the influence of employee engagement and work compliance on organizational commitment. The conclusion is that increasing employee engagement and work compliance can strengthen the organizational commitment of healthcare workers, both directly and through the mechanism of effort reward imbalance as a mediating variable.   Keywords: Employee Engagement, Work Compliance, Effort Reward Imbalance